# needing help on how to solve equations

• Aug 22nd 2010, 07:52 PM
Russell010887
needing help on how to solve equations
my last math class was in 2005 here it is 5 years later and i am still struggling with the same stuff basically i need to know the steps to solve equations i will set some examples

3(x - 1) - 12 = 0
-1(y + 3) = 10
-4x = 44
7 - z = 15
-7c + 1 = -20
5(3y - 2) = 16y
• Aug 22nd 2010, 11:19 PM
yeKciM
Quote:

Originally Posted by Russell010887
my last math class was in 2005 here it is 5 years later and i am still struggling with the same stuff basically i need to know the steps to solve equations i will set some examples

3(x - 1) - 12 = 0
-1(y + 3) = 10
-4x = 44
7 - z = 15
-7c + 1 = -20
5(3y - 2) = 16y

$\displaystyle 3(x-1)-12=0\Rightarrow 3x-3-12=0 \Rightarrow3x-15=0 \Rightarrow 3x=15 \Rightarrow x=\frac{15}{3} \Rightarrow x= 5$

$\displaystyle -4x=44 \Rightarrow 4x=-44 \Rightarrow x=\frac{-44}{4} \Rightarrow x=-11$

$\displaystyle 5(3y-2)=16y \Rightarrow 15y-10 = 16y \Rightarrow -10 = y \Rightarrow y=-10$

and so on :D
• Aug 23rd 2010, 02:18 AM
Educated
All of the questions are similar. First you expand the brackets and then get the letter on its own side.

Remember that:
$\displaystyle a(b+c)=ab+ac$
• Aug 23rd 2010, 02:24 AM
HallsofIvy
Quote:

Originally Posted by Russell010887
my last math class was in 2005 here it is 5 years later and i am still struggling with the same stuff basically i need to know the steps to solve equations i will set some examples

Whatever is done to the unknown value, undo it. You undo adding something by subtracting that same thing. You undo multiplying by division, etc. And, of course, you "undo" step by step in the opposite order in which it was "done". And whatever you do to one side of the equation you do to the other side as well.

3(x- 1)- 12= 0

If you were to start from "x" and calculate this you would: subtract 1, multiply by 3, then subtract 12. To "undo" that, you first add 12, then divide by 3 then add 1:"
3(x- 1)- 12+ 12= 0+ 12
3(x- 1)= 12

3(x- 1)/3= 12/3
x- 1= 4

x- 1+ 1= 4+ 1
x= 5

3(x - 1) - 12 = 0
Here, 1 is subtracted from x, then it is multiplied by 3, then 12 is subtracted. To "undo", add 12, then divide by 3, then add 1:
3(x- 1)- 12+ 12= 0+ 12
3(x- 1)= 12

3(x- 1)/3= 12/3
x- 1= 4

x-1+ 1= 4+ 1
x= 5

Try that on the rest of these

Quote:

-1(y + 3) = 10
-4x = 44
7 - z = 15
-7c + 1 = -20
5(3y - 2) = 16y
• Aug 24th 2010, 08:26 AM
Technet
Math.com Algebra Worksheet Generator
This is a big help. You can generate algrebra equations from simple one step equations to much harder equations.
You can also create an exam if you wish by putting a number of different equations to build up to getting harder as they go.

Also, If you struggle to work one out or want to know how to solve it. You can use this website to enter an equation that will solve it but also show you step by step how to do it.
Algebra.Help -- Equation Calculator

I'm currently learning to advance my own skills in math so these are helping a lot for me.